Combined use of improved maize hybrids and nitrogen application increases grain yield of maize, under natural Striga hermonthica infestation - Solomon, R.; Kamara, A.; Aliyu, K.T.; Ademulegun, T.; Mohammed, I.B.; Tofa, A.; Omoigui, L.O.; Adeleke, M. (Walter de Gruyter GmbH, 2024)
Striga hermonthica (Del.) Benth infestation is one of the major constraints to maize production in the Nigeria savannas. The application of nitrogen fertilizer to Striga-resistant hybrids may reduce Striga infection and increase grain yields. The objective of this study was to assess the performance of six maize hybrids at low (30 kg ha−1) and high (120 kg ha−1) nitrogen application under natural infestation with Striga in northern Nigeria in 2014 and 2015. The two nitrogen rates and the six hybrids were arranged in a split-plot design with three replications. The nitrogen treatment was assigned to the main plot while the maize hybrids were assigned to the subplot. Data were collected on number of emerged Striga plants, Striga damage score, total dry matter and grain yield. Results showed that the application of nitrogen at 120 kg ha−1 reduced the number of Striga plants by 58% compared to application at 30 kg N ha−1 in Kafin Madaki and by 48% in Tudun Wada. Nitrogen application at 120 kg N ha−1 also reduced Striga damage rating by 22% in Kafin Madaki and by 33% in Tudun Wada. Both the commercial hybrid (OBASUPER 1) and the susceptible hybrid (8338-1) exhibited higher Striga damage ratings compared to the new hybrids at both locations. Grain yield was 86 and 98% higher in Kafin Madaki and Tudun Wada, respectively, when N was applied at 120 kg N ha−1 than at 30 kg N ha−1. The hybrids M1124-3 and M1227-14 produced grain yields that were significantly higher than those of the other hybrids in all locations. Our results showed that the application of 120 kg N ha−1 to Striga-resistant maize hybrids will reduce Striga infection and increase grain yield.